CD103 Promotes the Pro-inflammatory Response of Gastric Resident CD4+ T Cell in Helicobacter pylori-Positive Gastritis - Chen, Peiyu; Ming, Siqi; Lao, Juanfeng; Li, Chunna; Wang, Hongli; Xiong, Liya; Zhang, Shunxian; Liang, Zibin; Niu, Xiaoli; Deng, Simei; Geng, Lanlan; Wu, Minhao; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
CD103 is considered as a surface marker for the resident immune cells. However, little is known about the intrinsic function of CD103 in infection and inflammation. In this study, we found that CD103 was highly expressed in CD4+T cells of the gastric mucosa from patients with H. pylori-positive gastritis. Mucosal resident CD103+CD4+T cells exhibited an increase in the CD45RO+CCR7− effector memory phenotype and high expression of the chemokine receptors CXCR3 and CCR9 compared with those in CD103−CD4+T cells. An In vitro coculture study demonstrated that H. pylori-specific antigen CagA/VacA-primed dendritic cells (DCs) induced proliferation and IFN-γ, TNF as well as IL-17 production by CD103+CD4+T cells from patients with H. pylori-positive gastritis, while blocking CD103 with a neutralizing antibody reduced proliferation and IFN-γ, TNF, and IL-17 production by CD103+CD4+T cells cocultured with DCs. Moreover, immunoprecipitation revealed that CD103 interacted with TCR α/β and CD3ζ, and activation of CD103 enhanced the phosphorylation of ZAP70 induced by the TCR signal. Finally, increased T-bet and Blimp1 levels were also observed in CD103+CD4+T cells, and activating CD103 increased T-bet and Blimp1 expression in CD4+T cells. Our results explored the intrinsic function of CD103 in gastric T cells from patients with H. pylori-positive gastritis, which may provide a therapeutic target for the treatment of gastritis.